Radical Care in Practice / Anti-Oppressive Child and Youth Care - Miller, Ryan C. (Journal of Childhood Studies, 2026)
This review examines Anti-Oppressive Child and Youth Care: Critical Conversations, edited by Andrea Christensen, a collection that brings together scholar-practitioners and youth to interrogate child and youth care in Canada. Grounded in storytelling and critical frameworks such as critical race theory, intersectionality, Indigenous relational ethics, fat studies, and anti-oppressive practice, the book addresses issues including anti-Black racism, ableism, anti-fat bias, and toxic positivity. This review highlights how the text moves beyond theory toward applied, reflexive praxis, particularly through its pedagogical design and critical reflection activities. It also considers the book’s Canadian focus and its relevance beyond that context.